Maximizing efficiency of alternation algorithms for hemodynamic optimization of the av delay of cardiac resynchronization therapy. - Whinnett ZI; Nott G; Davies JER; Willson K; Manisty CH; Kanagaratnam P; Peters NS; Davies DW; Hughes AD; Mayet J; Francis DP (Pacing & Clinical Electrophysiology, 2011)
During optimization of the atrioventricular (AV) delay of cardiac resynchronization therapy (CRT), it is not known exactly which windows of time around the transition are most informative for identification of the optimum. In 22 patients with CRT, we performed AV delay optimization using continuous noninvasive hemodynamics. We used signal-to-noise ratio to determine the most efficient averaging window location and width. We found that it is most efficient to position the averaging windows immediately before and immediately after the transition in AV delay. For example, skipping five beats after the transition decreases signal-to-noise ratio by 17.5% (P < 0.0001). Similarly, skipping five beats immediately before the transition reduces signal-to-noise ratio by 11.7% (P < 0.0001). The best choice of 'fixed' averaging window width was found to be six beats, with signal-to-noise ratio falling by, for example, 41% for a one-beat window (P = 0.0002). However, even better was to set the window width for each patient to match one respiratory cycle. We observed that the pre- and posttransition signal-to-noise ratio traces begin to diverge three beats after the transition in AV delay. We believe this represents the time taken for the peripheral response to pacing-induced changes in stroke volume to occur. The most efficient way to use alternating transitions for the hemodynamic optimization of CRT is to use an averaging window of one respiratory cycle, and not to skip any beats between the pretransition and posttransition averaging windows. (PACE 2011; 34:217-225)